The experience with colorectal cancer screening in the Czech Republic: the detection at earlier stages and improved clinical outcomes. (August 2020) - Kral, J.; Kojecky, V.; Stepan, M.; Vladarova, M.; Zela, O.; Knot, J.; Jakovljevic, M.; Kralova, Z.; Buresova, R.; Grega, T.; Bauman, D.; Kotyza, J.; et al.
Abstract: Objectives: Colorectal cancer (CRC) remains a major health burden. Although screening is recommended and considered beneficial, further data on its positive effects are needed for worldwide implementation. Study design: The aim of our national multicentre prospective observational study was to reveal and document clinicopathological differences in CRC diagnosed by screening and presented by disease symptoms as well as assess the efficiency of the screening programme in the Czech Republic. Methods: Between March 2013 and September 2015, a total of 265 patients were enrolled in 12 gastroenterology centres across the Czech Republic. Patients were divided into screening and symptomatic groups and compared for pathology status and clinical characteristics. Screening was defined as a primary screening colonoscopy or a colonoscopy after a positive faecal occult blood test in an average-risk population. Results: The distribution of CRC stages was significantly (statistically and clinically) favourable in the screening group (predominance of stages 0, I and II) compared with the non-screening group ( P  < 0.001). The presence of distant and local metastases was significantly less frequent in the screening group than in the symptomatic group ( P  < 0.001). Patients in the screening group had a higher probability of radical surgery (R0) than those diagnosed based on symptoms ( P  < 0.001). Systemic palliative treatment was indicated in two patients in the screening group compared with 23 patients in the non-screening group ( P  = 0.018). Conclusion: CRC diagnosed by screening disclosed less advanced clinicopathological characteristics and results in patients with a higher probability of radical surgery (R0) than diagnoses established based on symptoms, with subsequent management differing accordingly between both groups. These results advocate the implementation of a suitable worldwide screening programme. Highlights: Colorectal cancer (CRC) diagnosed by screening showed more favourable clinicopathological characteristics. Diagnosis of early-stage CRC contributes to better surgical removal (R0). CRC screening worldwide is beneficial.